Brutal Beauty : Aesthetics and Aspiration in Urban India - Menon, Jisha, 1972- (Book collections on Project MUSE., 2022)
"Taking Bangalore in southern India as its point of departure, this book explores the ways in which artists across India and beyond foreground neoliberalism as an inescapable market logic that permeates aesthetics, selfhood, and everyday life"--